2018
DOI: 10.1016/j.heliyon.2018.e00617
|View full text |Cite
|
Sign up to set email alerts
|

Induction of nerve growth factor by phorbol 12-myristate 13-acetate is dependent upon the mitogen activated protein kinase pathway

Abstract: Several small molecules have been identified that induce glial cells to synthesize and secrete nerve growth factor (NGF), a critical neurotrophin that supports neuronal growth and survival, and as such show promise in the development of drugs for the chemoprevention of Alzheimer's disease. To map the signal transduction cascade leading to NGF synthesis and secretion, cultured human glial cells were stimulated by phorbol 12-myristate 13-acetate (PMA), an agonist of Protein Kinase C. Changes in intracellular pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
(102 reference statements)
1
2
0
Order By: Relevance
“…However, it could be observed that both treatments resulted in a similar difference in proliferation rate in comparison to the control (Figure 5C). Reconciling with the previous finding that PMA induces nerve growth factor secretion and differentiation of PC12 cells, 44,45 we found that the PMA treatment alone can induce cellular transformation with neuritic outgrowth (Figure 5D). Regardless of this transformation, the cells did not express PSD-95 protein, as evidenced by the transient transfection of the PMA-treated cells with the plasmid pAAV ORANGE Dlg4 HaloTg KI (Figure 5E).…”
Section: Ltd Downregulated Pcreb and Sensitized Cscs To Metabolic Inh...supporting
confidence: 89%
“…However, it could be observed that both treatments resulted in a similar difference in proliferation rate in comparison to the control (Figure 5C). Reconciling with the previous finding that PMA induces nerve growth factor secretion and differentiation of PC12 cells, 44,45 we found that the PMA treatment alone can induce cellular transformation with neuritic outgrowth (Figure 5D). Regardless of this transformation, the cells did not express PSD-95 protein, as evidenced by the transient transfection of the PMA-treated cells with the plasmid pAAV ORANGE Dlg4 HaloTg KI (Figure 5E).…”
Section: Ltd Downregulated Pcreb and Sensitized Cscs To Metabolic Inh...supporting
confidence: 89%
“…It causes cellular survival increasing via NGF. Furthermore, in the absence of NGF, expression of preapoptotic protein increases, which is the result of cell‐activated transcription by the c‐Jun factor (Davis et al, ). However, several studies showed that NGF participates in other ways; not only to the cell cycle regulating pathways (Molloy, Read, & Gorman, ; Read, Molloy, & Gorman, ), but also it can increase the expression of genes such as Bcl‐2 by binding to the TrkA receptor, which increases the proliferation and survival of the target neuron (Figure ; path 3).…”
Section: Discussionmentioning
confidence: 99%
“…These considerable correlations were found between HUR1 and the genes of central triangle (CCW); CSTF2, CPSF7, and WDR33 (Table 4). (Davis et al, 2018). However, several studies showed that NGF participates in other ways; not only to the cell cycle regulating pathways ), but also it can increase the expression of genes such as Bcl-2 by binding to the TrkA receptor, which increases the proliferation and survival of the target neuron (Figure 3; path 3).…”
Section: Genesmentioning
confidence: 99%